The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00464-018-6363-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term results of a randomized study comparing high tie and low tie inferior mesenteric artery ligation in laparoscopic rectal anterior resection: subanalysis of the HTLT (High tie vs. low tie) study

Abstract: The IMA ligation level was unrelated to anastomotic leakage. No significant difference was detected in long-term results between HT and LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 32 publications
2
68
0
Order By: Relevance
“…Details of the included studies were collected (Table 1). Seven RCTs [18][19][20][21][22][23][24], 19…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the included studies were collected (Table 1). Seven RCTs [18][19][20][21][22][23][24], 19…”
Section: Study Characteristicsmentioning
confidence: 99%
“…RC/PC studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and two CC studies [44,45] published between 2011 and 2019 were analyzed, investigating 10,545 patients (including 4920 patients who underwent LCA non-preservation surgery and 5625 patients who underwent LCA preservation surgery) (CRC group). Additionally, 18 studies on RC alone (including 7 RCTs [18][19][20][21][22][23][24] and 11 RC/PC studies [25, 26, 28, 30-32, 35, 38, 39, 42, 43]) with 7142 patients (including 3468 patients who underwent LCA non-preservation surgery and 3674 who underwent LCA preservation surgery) were extracted for the subgroup analysis (RC group). Studies were assessed using the Cochrane and NOS scoring systems.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative randomized as well as no randomized trials have failed to show the superiority of a “high tie” in terms of LN harvest and OS [43-46]. Moreover, proximal ligation of the inferior mesenteric artery may compromise the blood supply to the proximal colon and increase the risk of anastomotic leakage [47].…”
Section: Clinical Studies Comparing the Extent Of Lymphadenectomymentioning
confidence: 99%
“…However, laparotomy cases were excluded, and the effects of high or low ligation of the IMA on long-term oncologic outcomes were not reported. In Fujii's study [12], laparotomy cases were included, and the results showed that the IMA ligation level was unrelated to anastomotic leakage. Further, there was no signi cant difference observed in the long-term outcomes in patients with or without LCA preservation.…”
mentioning
confidence: 99%